PENGARUH MODEL KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS II SD NEGERI 2 PASAR MADANG - Ujang Efendi; Dayu Rika Perdana; Frida Destini; Nurlita, Vira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of this research was the low learning outcomes of Pancasila Education of students and educators have not applied the cooperative learning model of picture and picture type. The purpose of the study was to determine the effect of the cooperative model of picture and picture type on the learning outcomes of Pancasila Education class II SD Negeri 2 Pasar Madang. This type of research used quantitative research with quasi-experimental method and research design using non-equivalent. The population of this study were 327 students, the research sample was students of class II A SD Negeri 2 Pasar Madang with a total of 26 students. The research sampling technique used purposive sampling technique. Hypothesis testing technique using simple linear regression test obtained amounted to 833.595 > 4, 26. The result of the research is that there is an influence of the cooperative model of picture and picture type on the learning outcomes of Pancasila Education class II SD Negeri 2 Pasar Madang.